Pengembangan Media Pembelajaran Koperasi Sekolah Augmented Reality Berbasis Experiential Learning - Annisya Annisya; Abdul Azis; Yogi Dwi Satrio; Syahrul Munir; Lisa Rokhmani; Ro’ufah Inayati; Agung Haryono (CV. Global Cendekia Inti, 2026)
This study aims to develop school cooperative learning media based on Augmented Reality (AR) with an experiential learning approach through the ADDIE development model. The background of this study is based on the low level of students' understanding of the concept of school cooperatives because the learning media used tend to be theoretical and do not provide direct learning experiences. This study uses a mixed method through questionnaires, interviews, and literature studies. The ADDIE stages, which include analysis, design, development, implementation, and evaluation, are used to design a prototype of a virtual school cooperative visit application. This learning media contains features on the history of cooperatives, management profiles, and financial reports in an interactive visual form. The validation results show that the application functions well, is safe to use, and has stable performance. The application of AR allows students to learn more realistically through exploratory experiences, helping them to understand the concept of school cooperatives more easily. Thus, this AR-based learning media can be an alternative solution to increase students' interest and understanding in learning about school cooperatives in a more contextual and enjoyable way.